Artificial Intelligence & Gamification for Dynamic Pricing in Retail - Onur GUVENC (Communications of International Proceedings, 2021)
This paper is a part of an ongoing series of papers, remaining a work in progress. The purpose of this segment of the larger body of work is to provide a literature review on the subject matter pertinent to the exploration of the topic of artificial intelligence (AI) and gamification for dynamic pricing in order to explore whether the concept of dynamic pricing will work in the retail marketplace. Within the context of this literature review, the researcher provide a definition and explanation of dynamic pricing, defines and explores the application of gamification within the context of dynamic pricing, and explores the application of AI in the definition of pricing. In addition, the researcher explore previous studies published within the extant body of literature, synthesizing this information to create a comprehensive picture of the topic. The paper concludes with the identification of the aspects of the paper that remain a work in progress and which will be presented in future submissions.
Keywords: artificial intelligence; AI; gamification; dynamic pricing; retail.